The effect of acute exercise on circulating immune cells in newly diagnosed breast cancer patients - Koivula Tiia; Lempiäinen Salla; Rinne Petteri; Rannikko Jenna H.; Hollmén Maija; Sundberg Carl Johan; Rundqvist Helene; Minn Heikki; Heinonen Ilkka (Nature Publishing Group, 2025)
The role of exercise in cancer prevention and control is increasingly recognized, and based on preclinical studies, it is hypothesized that mobilization of leukocytes plays an important role in the anti-tumor effect. Thus, we examined how 10-min acute exercise modulates immune cells in newly diagnosed breast cancer patients. Blood samples were taken at rest, immediately after exercise and 30 min after exercise and phenotypic characterization of major leukocyte subsets was done using 9-color flow cytometry. Total leukocyte count increased by 29%, CD8+ T cell count by 34%, CD19+ B cell count by 18%, CD56+CD16+ NK cell count by 130%, and CD14+CD16+ monocyte count by 51% immediately after acute exercise. Mobilization of CD45+, CD8+, CD19+, and CD56+CD16+ cells correlated positively with exercising systolic blood pressure, heart rate percentage of age predicted maximal heart rate, rate pressure product, and mean arterial pressure. Our findings indicate that a single bout of acute exercise of only 10 min can cause leukocytosis in breast cancer patients. Mobilization of leukocytes appear to be directly related to the intensity of exercise. It is possible that the positive effect of exercise on oncologic outcome might be partly due to immune cell mobilization as documented in the present study.